2019
DOI: 10.16965/ijar.2019.188
|View full text |Cite
|
Sign up to set email alerts
|

Formalin Induced Nuclear Abnormalities in Relation With Duration of Exposure: A Study of Formalin Exposed Anatomists, Attenders and Students

Abstract: Background: Exposure of Genotoxic agents like formalin causes cancer. The duration of exposure and the quantity of exposure plays an important role in inducing the nuclear abnormalities. The nuclear abnormalities are BN, KR, KL.Objective: This study provides an easy and inexpensive way to assess the formalin induced nuclear abnormalities in different groups with different duration of exposure.Materials and methods: Fifty individuals with different duration of exposure were included in our descriptive study. Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In the present study, the relationship between exposure time during the day and mean percentage of MN in the buccal cells was significant (P=0.03), which is consistent with the findings of Abdel Aziz et al (19). Furthermore, Sivasankarinatarajan et al revealed a positive correlation between time of exposure and carcinogenesis (31). The results of these studies could indicate that the number of MN increases with extended exposure time during the day (19,31).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the relationship between exposure time during the day and mean percentage of MN in the buccal cells was significant (P=0.03), which is consistent with the findings of Abdel Aziz et al (19). Furthermore, Sivasankarinatarajan et al revealed a positive correlation between time of exposure and carcinogenesis (31). The results of these studies could indicate that the number of MN increases with extended exposure time during the day (19,31).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Sivasankarinatarajan et al revealed a positive correlation between time of exposure and carcinogenesis (31). The results of these studies could indicate that the number of MN increases with extended exposure time during the day (19,31).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation